2014
DOI: 10.19026/rjaset.8.1006
|View full text |Cite
|
Sign up to set email alerts
|

Potential uses of Waste Sludge in Construction Industry: A Review

Abstract: Waste generation and management is becoming a global challenge resulting into increased environmental concern. Waste management and recycle into a sustainable construction materials as proved to be an alternative for waste disposal helping out in the area of environmental pollution and economic. In recent years various type of waste has been used/reused in the development of sustainable construction materials. This study reviews various attempts that have been made to use sludge from different plants in constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 33 publications
0
19
0
2
Order By: Relevance
“…In recent years, many researchers have studied the use of WTP sludge [28] in degraded areas [13,14], coagulant regeneration [15], and reuse in the construction industry as a replacement for, or addition to, the traditional raw materials in the production of cement [16,17,18], concrete [3,11,19,20,21,22], ceramic [23,24,25,26,27,44], soil-cement [29], and mortars [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researchers have studied the use of WTP sludge [28] in degraded areas [13,14], coagulant regeneration [15], and reuse in the construction industry as a replacement for, or addition to, the traditional raw materials in the production of cement [16,17,18], concrete [3,11,19,20,21,22], ceramic [23,24,25,26,27,44], soil-cement [29], and mortars [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Johnson et al, [27], mixed water treatment sludge with excavated soil waste to make bricks and the study concluded that, 15% water treatment sludge was the maximum addition to achieve first degree brick. In a research conducted in Netherland by Feenstra et al, [28], the researchers successfully produced brick with clay and addition of sludge in which the assessment was based on "production technique and environmental performance (leaching behaviour)".…”
Section: Production Of Brickmentioning
confidence: 99%
“…The mineralogical constituents were mainly calcite and clay materials which enabled it for use in cement mortars. Johnson et al (2014) also reported that the use of different types of sludge as a raw material in the construction industry is practicable without compromising the material requirements according to available standard.…”
Section: Introductionmentioning
confidence: 99%